Temas relevantes do processo administrativo sancionador no âmbito do direito do consumidor - Santos, Marcelo Fernando Neri (2022)
This dissertation is intended to address relevant issues of the administrative sanctioning process, specially those that are related with procedures used by the State for supervising and punishing infringing practices in the consumer’s market. In order to make this research possible, specialized bibliography analysis, as well as, decisions rendered by the superior courts on the subject were used. Sometimes the deductive method was used, at other times the inductive method. Thus, it was deemed important to emphasize, in the first chapter, the historical aspects that, for this study, constitute the foundation for the consumer’s protection rules, with emphasis on the birth of the consumer society - and its exceptionality. Then, in the second chapter, we chose to face two elements of administrative/public law that justify the use of the administrative sanctioning process as a relief instrument, and customer protection, since that they authorize the State's intervention on matters of interest, that are, to begin with, exclusive of the individual. Next, we sought to understand how the consumer protection agencies are organized, and what are their attributions. Finally, in the fourth chapter, there was a discussion about the jurisdiction conflict; the definition of the legal infraction hypotheses; if there is the need, or not, to examine the supplier's volition – culpability – and, finally, the structure of the penalty and the decision act that attributes the reprimand to the supplier. It should be noted that all four topics would be worthy of an exclusive study. However, the purpose of this paper is to highlight the importance and timeliness of the debate regarding the administrative sanctioning process in the context of consumer law and the complexity of some of the most recurrent issues